In vitro phenotypic screening of 7-chloro-4-amino(oxy)quinoline derivatives as putative anti-Trypanosoma cruzi agents (2014)
In this study, a series of 22 pre-synthesized 7-chloro-4-mino(oxy)quinoline derivatives was assayed in vitro as potential antichagasic agents. A primary screening against Trypanosoma cruzi epimastigotes and a non-specific cytotoxicity assay on murine fibroblasts were simultaneously performed, resulting quinolines 3, 7 and 12 with great selectivity (SI) on the extracellular parasite (SI7, SI3 , SI12 and SIBZ >9.44). Therefore, the activity of these derivatives was evaluated on intracellular amastigotes, achieving derivative 7 the best SI (SI = 12.73). These results, supported by the in silico prediction of a good oral bioavailability and a suitable risk profile, propose the 4-amino-7-chloroquinoline scaffold as a potential template for designing trypanocidal prototypes.